Versatility of Kinesio-Taping in Postoperative Swelling, Pain, and Trismus After Surgical Removal of Impacted Lower Third Molars - Dani Mihir Tusharbhai; Mohan Baliga; Aananya Mishra (Wolters Kluwer Medknow Publications, 2020)
Introduction: Although extraction of an impacted lower third molar is a routine procedure, postoperative morbidities typically include swelling, pain, and trismus that increase patient suffering postoperatively. The appliance of Kinesio tape (KT) improves the blood and lymph flow, removing congestions of lymphatic fluid and hemorrhages. The aim of the present study was to evaluate the efficacy of the application of KT on postoperative swelling, trismus, and pain thereby improving the patient condition and well-being. Materials and Methods: Thirty patients with surgical removal of third molars were enrolled and randomized into two treatment groups (with/without KT). The tape was applied immediately after surgery and removed on fifth postoperative day. Facial swelling was measured using a five-line measurement at six specific time points. Pain scores were assessed using a visual analog scale, and mouth opening ability was assessed by means of calipers. The data were analyzed and compared using an independent sample t test. Results: The application of KT significantly reduced postoperative swelling, pain, and trismus. Moreover, patients with KT showed a considerably lower morbidity rate. Conclusion: The application of KT is a self-effacing, less traumatic, economical approach, which is free from an adverse reaction and improves patients' quality of life. Besides, it can be seen as an adjunct/alternative to steroids or supplementary medications.